Conflicts of interest among authors of the ESC guidelines for the management of atrial fibrillation between 2010 and 2020. (3rd October 2022) - Schneider, B; Stoellberger, C
Abstract: Background: In 2011, the Institute of Medicine (IOM) published standards for developing trustworthy clinical practice guidelines. It is recommended that "Whenever possible guideline development group members should not have conflicts of interest (COIs)... Members with COIs should represent not more than a minority of the guideline development group members. The chair or cochairs should not be a person with COIs." Purpose: Aim of the present study was to assess if the ESC guidelines for the management of atrial fibrillation are in accordance with the standards proposed by the IOM. Methods: The declaration of COIs from task force members (TFM) and reviewers of the ESC atrial fibrillation guidelines 2010, 2016 and 2020 were retrieved from the ESC homepage. The number and the type of COIs were assessed for each guideline and compared. Results: Regarding the 2010 guidelines, 17 of 25 TFM (68%) declared COIs. Overall, 148 COIs were reported (8.7±10.2 per member, range 1–44). The chairperson declared 11 COIs. 15 of 25 TFM (60%) received direct personal payments (5.9±7.3 COIs per member, range 1–30). Research contacts were reported by 13 TFM (52%). Among the guideline reviewers, 14/26 (54%) indicated any COI (5.1±3.3 per reviewer, range 2–14). Regarding the 2016 guidelines, 14 of 17 TFM (82%) declared COIs. Overall, 182 COIs were reported (13.0±10.4 per member, range 1–32). The chairperson of the task force had the second most COIs (n=30). 14 of 17 TFM (82%) received direct personal payments (7.7±7.4 COIs per member, range 1–22). Research funding of the department was reported by 10 TFM (59%). Among the guideline reviewers, 63/79 (80%) reported any COI (7.5±6.8 per reviewer, range 1–34). In 2020, 21 of 24 TFM (87%) indicated any COI. Overall, 140 COIs were reported (6.7±4.5 per member, range 1–20). The chairperson of the task force declared 5 COIs. 18 of 24 TFM (75%) received direct personal payments (4.1±3.1 COIs per member, range 1–10). Research funding of the department was reported by 13 TFM (56%). Among the guideline reviewers, 87/105 (83%) reported COIs. Comparing the guidelines between 2010 and 2020, there is an increasing proportion of TFM with COIs (from 68% in 2010 to 87% in 2020), and the proportion of TFM receiving personal payment remains high (75% in 2020). In addition, more guideline reviewers reported COIs (54% in 2010 vs 83% in 2020). Overall, the number of COIs per TFM was slightly decreasing in 2020. Companies marketing direct oral anticoagulants were most frequently mentioned in the COI declarations of the TFM in 2016 and 2020. Conclusion: The high and increasing rate of TFM and reviewers with COIs is not in accordance with the recommendations of the IOM. Since COIs can influence healthcare decision makers and may consciously or unconsciously influence choices made throughout the guideline development process, the ESC should follow the standards of the IOM. Funding Acknowledgement: Type of funding sources: None.